2006
DOI: 10.1111/j.1526-4610.2006.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Tension‐Type Headache and Migraine in Adolescents: A Student‐Based Study

Abstract: Our data strongly support continuum hypothesis. In early adolescence headaches might present with mixed headache characteristics. Age and gender have some influence on headache characteristics, particularly on migraine. The sensitivity and specificity of case definition criteria of ICHD-2 for adolescent migraine is moderate and need to be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 19 publications
10
47
1
2
Order By: Relevance
“…Hershey et al 38 observed virtually the same findings among 3e18-yearold migraineurs, and Eidlitz-Markus et al 39 did so as concerns the frequency, duration and vomiting in a 6e18-year-old paediatric population. Winner et al 31 and Karli et al 32 compared the trends between 12e14 and 15e17-year age groups, and reached similar conclusions to ours in respect of photophobia, phonophobia, nausea and vomiting; Karli et al 32 additionally observed an increasing trend of a pulsating character and a unilateral location. In a comparison of migraine groups aged 3e10 and 10e14 years, Gherpelli et al 30 detected a significant increase only in the pulsating character.…”
Section: Phonophobia (G) Photophobia (G) Unilateral (G) Pulsating (B)supporting
confidence: 73%
See 1 more Smart Citation
“…Hershey et al 38 observed virtually the same findings among 3e18-yearold migraineurs, and Eidlitz-Markus et al 39 did so as concerns the frequency, duration and vomiting in a 6e18-year-old paediatric population. Winner et al 31 and Karli et al 32 compared the trends between 12e14 and 15e17-year age groups, and reached similar conclusions to ours in respect of photophobia, phonophobia, nausea and vomiting; Karli et al 32 additionally observed an increasing trend of a pulsating character and a unilateral location. In a comparison of migraine groups aged 3e10 and 10e14 years, Gherpelli et al 30 detected a significant increase only in the pulsating character.…”
Section: Phonophobia (G) Photophobia (G) Unilateral (G) Pulsating (B)supporting
confidence: 73%
“…Higher rates of headache frequency, a uni/bilateral location, photophobia and photophobia were seen in girls, and of vomiting in boys. Ando et al 37 and Karli et al 32 reported similar findings, but Akyol et al 13 observed slightly higher rates of a pulsating character, photophobia and phonophobia in boys, and higher rates of nausea or vomiting in girls. Vomiting and phonophobia were more common in boys in the study by Wö ber-Bingö l et al, 35 while girls complained more commonly of the aggravating effect of physical activity.…”
Section: Phonophobia (G) Photophobia (G) Unilateral (G) Pulsating (B)mentioning
confidence: 80%
“…Their fi ndings were confi rmed by other authors. 2,3,8,9 The problem with overlapping headache is more prominent for children and adolescents because of some accepted revisions in the criteria for migraine in ICHD-II. 10 The revisions include shorter duration of migraine attack in children -1 hour (instead of 4 hours for adults); either unilateral or bifrontal or bitemporal location (instead of only unilateral location for adults); photo-or phonophobia (instead of photo-and phonophobia for adults).…”
Section: Reclassification Of Overlapping Headache By Proposed Additiomentioning
confidence: 99%
“…The precise diagnosis of the type of headache is very important for adequate treatment but is hindered by the overlap of the symptoms of these two entities. [1][2][3] The overlapping characteristics of MWA and episodic TTH (ETTH) led to the conclusion that distinction between these two entities may be diffi cult or even impossible. [4][5][6] A number of primary headaches could be classifi ed as either MWA or TTH, the so called "overlapping headache".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation